A little more social enaction than that: comment on Arango (2019). (April 2019) - McGann, Marek
In his article "From Sensorimotor Dependencies to Perceptual Practices", Alejandro Arango presents a case for socialising enactive perception. While noting the importance of understanding perception as embodied, he argues that addressing just the issues of embodiment is not enough, that the socially situated and conditioned character of bodies, and the practices involved in perception, must be given full account. In surveying the current state of enactive theories of perception Arango dismisses what he terms "autopoietic" enactivism as only "hand waving" on the manner in which social aspects of life affect or transform bodily perception and action. In this commentary I argue that Arango has overlooked an important body of research by researchers in the "life-mind" or "sense-making" domain of enactive thinking. This literature addresses the dynamics of sociality in perception and action, and while greater integration between the descriptions of embodied action and social engagement is needed, significant progress has been made on this matter in recent publications.